1989
DOI: 10.1021/bi00435a028
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the conformation of glutamate dehydrogenase, the state of association of its subunit, and catalytic function

Abstract: The fluorescence and phosphorescence properties of the tryptophan residues in glutamate dehydrogenase were utilized to probe the conformation of the macromolecule at various states of aggregation of its subunits (hexamer, trimer, and monomer) in guanidine hydrochloride. According to the phosphorescence lifetime no gross alteration in the conformation of the protein follows from complete dissociation of the hexamer into native monomer, implying that the native fold is stabilized exclusively by intrasubunit bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The large window of lifetimes, from sub-milliseconds to seconds, makes detection of conformational changes straightforward and offers very high sensitivity, particularly for buried Trp residues that exhibit a long . In numerous studies, measurements of have revealed subtle variations in the structure of proteins that could not be detected by other means (17)(18)(19)30). Furthermore, wherever parallel measurements have been performed, changes in the protein structure detected by other techniques have always been reflected by a substantial alteration of .…”
Section: Discussionmentioning
confidence: 99%
“…The large window of lifetimes, from sub-milliseconds to seconds, makes detection of conformational changes straightforward and offers very high sensitivity, particularly for buried Trp residues that exhibit a long . In numerous studies, measurements of have revealed subtle variations in the structure of proteins that could not be detected by other means (17)(18)(19)30). Furthermore, wherever parallel measurements have been performed, changes in the protein structure detected by other techniques have always been reflected by a substantial alteration of .…”
Section: Discussionmentioning
confidence: 99%
“…These features have proven to exhibit an unparalleled sensitivity to the conformational state of the macromolecule with sable to monitor even subtle alterations of the native fold often undetected by ordinary spectroscopic techniques. Examples are the relatively large variations of s often induced by ligand binding (metal ions [5,10], substrates and cofactors [11][12][13]), subunit association (14), the addition of stabilizing (15) or denaturing (16) agents and cosolvents (17), dehydration (18) or ice formation (19), besides variations of temperature and pressure (20).…”
Section: Introductionmentioning
confidence: 99%
“…These features have proven to exhibit an unparalleled sensitivity to the conformational state of the macromolecule with table to monitor even subtle alterations of the native fold often undetected by ordinary spectroscopic techniques. Examples are the relatively large variations of τ often induced by ligand binding (metal ions [5,10], substrates and cofactors [11‐13]), subunit association (14), the addition of stabilizing (15) or denaturing (16) agents and cosolvents (17), dehydration (18) or ice formation (19), besides variations of temperature and pressure (20).…”
Section: Introductionmentioning
confidence: 99%